FUNGSIONALITAS DAN EFISIENSI RUANG BACA DI TERMINAL DUNGINGI KOTA GORONTALO DENGAN PENDEKATAN “SMART BUILDING” - Ajami, Frans Mitran; Bakari, Zulkifli (ANALOGI : Arsitektur, Lingkungan Binaan & Planologi, 2024)
Indonesia is a country with very low reading interest. Technological developments can be utilized to change lazy reading habits into reading hobbies through interactive features such as highlighting, digital notes, and automatic recommendations to make the reading experience more interesting and personal. With advanced technology, someone can read anywhere and anytime, including while waiting, which is often an unproductive time. This study uses a qualitative method with an architectural approach to understand aspects of space, design approaches, and human interaction with the built environment. The research location is focused on the Dungingi Terminal, Gorontalo City, the data includes primary and secondary, data collection techniques using observation techniques, interviews, surveys, and documentation. Data analysis uses data display, data grouping, data reduction, and data interpretation. The results of the study indicate that re-growing people's interest in reading does not need to be in a library building, but it can also be done in public buildings, so that increasing lumeration and literacy in the community goes well. In the reading room with an architectural approach concept with "Smart Building", the selection of building elements in the form of energy-saving needs, the use of technology to support indoor needs in the form of electronic reading media procurement, and in the process of operating a smart building system. The world of architecture is challenged to be able to carry out or design public facilities that combine various functions, such as transportation and education, in one building. This can maximize the use of space and increase added value for the community, such as a terminal that functions as a reading room. The application of flexible design allows public spaces to be changed or used for various purposes, without sacrificing comfort or primary functionality.